Tracing metastatic spread in pediatric solid tumors using copy number and targeted deep sequencing - Andersson, Natalie ; 0000-0002-3643-4404; Ferro, Michele; Jansson, Caroline; Chattopadhyay, Subhayan ; 0000-0002-8599-2971; Karlsson, Jenny; Gisselsson, David (Journal of Pathology, 2025)
The most common cause of death in pediatric cancer patients is a treatment-resistant tumor, compounded by metastatic spread, making surgery, radiation therapy, and chemotherapy unfeasible as curative treatment options. However, the mechanisms behind metastatic spread in pediatric tumors remain largely unexplored. We conducted whole-genome copy number profiling on 171 primary tumor and metastases samples from 17 patients with neuroblastoma, Wilms tumor, or gonadal tumors, and performed targeted deep sequencing on a subset. Phylogenetic reconstruction enabled spatiotemporal tracking of subclones. In total, 11 of 17 patients displayed at least one metastasis arising earlier, defined as occurring before the most recent common ancestor in the primary tumor. In eight patients, metastatic spread was observed several times during tumor evolution, with different subclones from the same primary tumor having metastatic capability, even colonizing the same site. Strikingly, dissemination between metastases (intermetastatic spread) occurred in eight of nine patients with metastases in at least two different sites, indicating that this is a common phenomenon in pediatric malignancy.
Keywords: Phylogenetics; Wilms tumor; Rhabdomyosarcoma; Neuroblastoma; Gonadal tumors; Metastasis